Contabilidad de fluctuaciones de la producción en México - Arturo Antón Sarabia (Banco de México, 2008)
– During the last years, Mexico has registered relatively large output falls. The business cycle accounting method of Chari, Kehoe and McGrattan (2007) is applied to the two most recent recessions in Mexico (including the 'Tequila crisis') in order to understand what are the most important wedges driving output over the cycle and to evaluate to what extent such falls may be smoothed. First, it is found that efficiency and labor wedges may reasonably account for output fluctuations in each recession. Second, counterfactual exercises suggest that the elimination of distortions represented in terms of the efficiency wedge might result in output falls about one third of those observed in the data.
Keywords: E32; O41; O54; 330; Business cycle accounting; Tequila crisis; Total factor productivity; Mexico; Konjunktur; Produktivität; Mexiko